Identification and Preservation of Intestinal Parasites Using Methylene Blue-Glycerol Mount: A New Approach to Stool Microscopy - Vinay Khanna; Kriti Tilak; Shihnin Rasheed; Chiranjay Mukhopadhyay (Journal of Parasitology Research)
We have tried a new approach to routine stool microscopy by using a combination of methylene blue and glycerol in wet mount preparation of fresh faecal samples for the demonstration of medically important intestinal parasites. This combination was evaluated for finding differences in the details and clarity of morphology and internal structures of parasites under low- and high-power microscopy as compared to iodine and saline mount. It was further evaluated to estimate the time taken by methylene blue-glycerol mount to dry up as compared to iodine and saline wet mount.